2020
DOI: 10.1097/dss.0000000000002028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Functionality in Elderly Patients When Determining Appropriate Treatment for Nonmelanoma Skin Cancers

Abstract: BACKGROUND The treatment of nonmelanoma skin cancer (NMSC) in the elderly population is a source of significant debate. Mohs micrographic surgery (MMS) is a highly effective treatment option yet not every patient with a cutaneous malignancy that meets appropriate use criteria (AUC) should be treated with surgery. OBJECTIVE The purpose of this study was to use the Karnofsky Performance Status (KPS) scale to categorize the functional status of patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Treatment for nonmelanoma skin cancer (in particular basal cell carcinoma) in the elderly carries considerable controversy and functional needs must be assessed for each patient. 2 Although this tumor was unlikely to affect our patient's mortality, it was causing significant morbidity and agitation. We opted to perform as simple and as functional of a repair with the fewest trips to the surgical suite.…”
Section: Discussionmentioning
confidence: 77%
“…Treatment for nonmelanoma skin cancer (in particular basal cell carcinoma) in the elderly carries considerable controversy and functional needs must be assessed for each patient. 2 Although this tumor was unlikely to affect our patient's mortality, it was causing significant morbidity and agitation. We opted to perform as simple and as functional of a repair with the fewest trips to the surgical suite.…”
Section: Discussionmentioning
confidence: 77%
“…6 Fortunately, a study on patients older than age 75 years, and even older than age 85 years, 7 found that patients who were more functional were more likely to receive surgery. Another study 8 found that patients who were less functional were more likely to undergo other treatment types, even when they met appropriate use criteria for Mohs surgery. Among older patients, Mohs surgery is associated with an improvement in survival of almost 2 years vs similar cohorts who received other treatments.…”
mentioning
confidence: 99%